Sonhos e insônia: o uso de imagens oníricas como instrumento terapêutico no auxílio ao tratamento de indivíduos insones - Catta-Preta, Marisa Vicente (2009)
This work had as a goal to observe and analyze the dream images as a therapeutic instrument in the assistance of the treatment for patients with primary, chronic and intermediate insomnia. Group work was used in the analyses of dream reports from individuals with insomnia in fifteen meetings. The usage of remembered dreams allowed us to access to unconscious contents and from that we worked therapeutically the conflicts that were presented and that could be interfering in the insomnia. The subjects were three adults of the female sex. The choice of subjects followed the criteria of the diagnoses of chronic and intermediate insomnia, and also the criteria of availability for research, furthermore they had to remember their dreams on a regular basis. We asked the subjects to participate in an individual interview before attending the group meetings, answering questions about their sleep, dreams and also take a polysomnography so that the quality of their sleep could be analyzed. During the meetings the remembered dreams were reported and worked through with the group from the personal associations of the dreamer. Through the analyses of the dream series it was possible to present to the subjects the emotional aspects that were about an ordinary theme, which brought about a certain repetition and should be elaborated and integrated by the subject. Also, during this period, we asked the subjects to register in a diary, supplied by the researcher, the number of hours of sleep, the number of interruptions during the night, if the dream in general was good or bad and the dreams that were remembered. The method used was qualitative, and from that we analyzed the process of each subject. The data acquired was analyzed to the light of analytical psychology, following the reference of dream analyses of this approach. After the termination of the groups, the subjects took a new polysomnography in the Sleep Institute of Santos (Instituto do Sono de Santos); they did a final and individual interview with the same questions about sleep and dream. Considering the amount of hours of sleep, the quality of sleep and the individual s perception of a better quality of life as criteria for improvement, we can say that the group work with the dream images helped in the treatment of the subjects insomnia. Through the dream analyses it was possible to present the subjects the emotional aspects that were about an ordinary theme, that should be elaborated and integrated by the subject